2013
DOI: 10.4236/jacen.2013.24012
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the insecticidal limonoid content of commercial biopesticides and neem extract using solid phase extraction

Abstract: Neem extract is an alternative insecticide for organic farming and is an allowed component for commercial biopesticide in Korea. However, crop protection properties are not consistent in commercial products. In this report, quantitative analysis of commercial biopesticides for the four insecticidal limonoids of neem extract-azadirachtin A, azadirachtin B, deacetylsalannin and salannin, was conducted through solid phase extraction method with lipophilic-hydrophilic balanced material. The recoveries of the four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 25 publications
0
18
0
4
Order By: Relevance
“…, , . , , , (Lee et al, 2013;Lim et al, 2014a;Lim et al, 2014b) (Kim et al, 2015;Choi et al ., 2016a) . ,…”
Section: Research Articleunclassified
“…, , . , , , (Lee et al, 2013;Lim et al, 2014a;Lim et al, 2014b) (Kim et al, 2015;Choi et al ., 2016a) . ,…”
Section: Research Articleunclassified
“…Recently, Lee et al reported the analytical method using HLB SPE and UPLC for the quantitative analysis of bioactive limonoids in the biopesticides containing neem extract [33]. First, the HLB clean-up method was applied to the purification method for quantitation of alkaloidal matrines, which were spiked at a concentration of 10 mg·L −1 in the biopesticide containing neem extract.…”
Section: Application Of Hlb Spe For the Matrinesmentioning
confidence: 99%
“…The HLB clean-up procedure as reported by Lee et al was followed [33]. The HLB cartridge was first conditioned with 2 mL MeOH and 2 mL distilled water (DW), then the sample was loaded and washed with 5% aqueous MeOH (2 mL).…”
Section: Clean-up Of Alkaloidal Matrines Using Hlb Spementioning
confidence: 99%
See 1 more Smart Citation
“…최근 님, 고삼, 계피 및 마늘 추출물 함유 유기농자재 중 작물보호활성 성분을 지표성분으로 설정하고, hydrophilic liphophilic balance (HLB), ENVI-Carb 및 C18 카트리지를 이용한 고체상 추출법(solid phase extraction, SPE)과 ultra-performance liquid chromatography (UPLC) 및 GC 를 활용한 지표성분 분석법이 보고되었다 (Lee et al, 2013: Lim et al, 2014aLim et al, 2014b;Lim et al, 2014c …”
unclassified